Rocha pears stored under controlled atmosphere with ultra-low and low O2 associated with different CO2 levels Peras ‘rocha’ armazenadas em atmosfera controlada com ultrabaixo O2 e com baixo O2 associado a diferentes teores de CO2 - de Martin M.S. (2017)
© 2017, Sociedade Brasileira de Fruticultura. All rights reserved.The storage of ‘Rocha’ pears under controlled atmosphere (CA) preserves fruit quality for long periods. However, inadequate CA conditions might impair ripening and lead to flesh browning. This research was carried out to assess the effects of CA with ultra-low (ULO), and low O2 (LO) associated with different CO2 levels on ripening and occurrence of flesh browning in ‘Rocha’ pears. Treatments evaluated were: pO2 = 0.5 kPa (ULO) and pCO2 < 0.03 kPa; pO2 = 1.0 kPa (LO) and pCO2 < 0.03 kPa; pO2 = 1.0 kPa and pCO2 = 1.0 kPa; pO2 = 1.0 kPa and pCO2 = 2.0 kPa; and pO2 = 1.0 kPa and pCO2 = 3.0 kPa. A completely randomized experimental design was used, with four replicates. Fruits were harvested in Vacaria, RS, and stored under five CA conditions during 270 days (-0.5±0.1 ºC and relative humidity of 96±2%). Fruits were assessed after CA storage for respiratory rate, ethylene production, skin color, flesh firmness, texture, titratable acidity (TA), soluble solids content (SSC), sensory attributes, flesh browning incidence and severity and flesh color. Fruits stored under LO with pCO2 < 0.03 kPa had higher flesh firmness and more yellow skin color than fruits stored under other CA conditions. Sensory attributes, SS and TA of fruits were not affected by CA conditions. Fruit stored under LO with pCO2 = 3.0 kPa had the highest incidence (48%) and severity of flesh browning. The pO2 = 0.5 kPa and pCO2 < 0.03 kPa and pO2 = 1.0 kPa and pCO2 = 1.0 kPa conditions are the most suitable for the CA storage of ‘Rocha’ pears.